Ethylene / alpha-olefin copolymer as well as preparation method and application thereof
Ethylene/α-olefin copolymers with controlled density and temperature ranges, produced using a dual catalyst system, address decomposition and PID issues in solar cell sealants, improving device efficiency and resistance.
Patent Information
- Application Number
- CN202411698166.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Existing solar cell sealants, such as ethylene/vinyl acetate copolymers, decompose under long-term sunlight exposure, producing components that reduce the service life and efficiency of solar cell devices, and high voltage applications lead to potential-induced degradation (PID) due to low volume resistance and resistance differences.
Development of ethylene/α-olefin copolymers with specific density, melting temperature, and crystallization temperature ranges, along with a controlled molecular weight distribution, to achieve high volume resistivity and light transmittance, using a dual catalyst system to regulate polymer properties.
The ethylene/α-olefin copolymers exhibit high volume resistance and light transmittance, delaying PID phenomena and enhancing module efficiency in solar cell modules.
Smart Images

Figure SMS_43 
Figure SMS_44 
Figure SMS_45
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to an ethylene / -Olefin copolymers and preparation methods and applications thereof. Background Art
[0002] In order to solve environmental and energy problems, under the "dual carbon" policy advocated in China and even the world, solar cells as a new type of clean energy that can utilize sunlight have received widespread attention. Today, solar cells are usually assembled in modules and used on the roof of a building or outdoors. Solar modules are stacked in order and divided into solar cell module protection sheet (transparent protection member on the surface side) / solar cell sealant / crystalline solar cell device / solar cell sealant / solar cell module protection sheet (back protection member).
[0003] As solar cell sealants, ethylene / vinyl acetate copolymers or ethylene / -olefin copolymers, etc. In addition, in solar cell sealants, considering the use scenario, it is necessary to meet long-term weather resistance requirements, and light stabilizers are usually included as additives, and in addition, considering the adhesion of transparent surface side protection members or back protection members represented by glass, silane coupling agents, etc. are usually added to solar cell sealants. However, if ethylene / vinyl acetate copolymers are used as a constituent material of solar cell sealants, under long-term sunlight exposure, ethylene / vinyl acetate copolymers will decompose in the battery assembly to produce components such as acetic acid gas, which will greatly affect the service life and battery efficiency of the solar cell device.
[0004] In addition, the recent rise of solar power generation has led to the continuous expansion of the scale of power generation systems (such as super solar), and in order to reduce the power loss during transmission, the most direct measure is to increase the voltage of the power transmission system. As the voltage of the power transmission system increases, the potential difference between the frame and the battery in the solar cell module increases. The frame of the solar cell module is usually grounded, so its voltage is 0V. When the system voltage of the solar cell array is 600V to 1000V, the potential difference between the frame and the battery is 600V to 1000V, and the high voltage application state is maintained for a long time, so the working temperature during the day will be much higher than that at night. Compared with sealants, glass has a lower resistance, and due to the insertion of the frame, a high voltage is generated between the glass and the battery. In the solar cell module used in this state, the output efficiency is greatly reduced due to the phenomenon of potential induced degradation (PID). Therefore, in order to solve these problems, a solar cell sealant film with higher volume resistance is required that is in direct contact with the solar cell device.
[0005] Volume resistance or specific resistance (ρ), known as electrical resistance, is defined as 1m 3 The resistance between the contact surfaces of the material, people hope to obtain the volume resistance described therein, to achieve the corresponding predetermined range in different applications, and can be made into molded products. For example, in the field of electrical insulation materials for high-voltage power cables, low-density polyethylene, cross-linked polyethylene, etc. prepared under high-voltage conditions have excellent electrical properties and are widely used. The high volume resistance of this material can achieve the purpose of reducing power loss. In the insulating material of the power cable, the inside of the conductor can be heated to a high temperature of 90°C by the heat generated by the passage of current, while the outside of the conductor remains at room temperature. However, when a continuous current passes through traditional polyethylene, the volume resistance near the internal conductor often decreases significantly.
[0006] Therefore, how to develop a solar cell sealing material with high volume resistivity, high PID resistance and light transmittance has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides an ethylene / -olefin copolymer and its preparation method and application, by defining ethylene / -The density, melting temperature and crystallization temperature of olefin copolymers enable the encapsulation materials made from them to obtain high volume resistivity and excellent insulation properties, as well as high light transmittance. They can be widely used in the electrical and photovoltaic fields, especially in solar cell modules, where they can delay the PID phenomenon and achieve excellent module efficiency.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In the first aspect, the present invention provides an ethylene / -olefin copolymer, the ethylene / -Olefin copolymers have the following characteristics:
[0010] (a) the ethylene / - the density of the olefin copolymer is 0.84-0.90 g / cc;
[0011] (b) a melting temperature Tm having a maximum peak in a curve obtained by a differential scanning calorimeter is 40-90°C;
[0012] (c) a crystallization temperature Tc having a maximum peak in a curve obtained by a differential scanning calorimeter, wherein the melting temperature Tm is 15-45°C higher than the crystallization temperature Tc, that is, 15°C≤Tm-Tc≤45°C.
[0013] The ethylene / -Olefin copolymers are generally low-density polymers, in which there is a mixture and a small amount of -High density areas of olefin-based monomers, also mixed and introduced a large amount of - low density region of olefin-based monomers. -The Tm-Tc value of the olefin copolymer is greater than or equal to 15°C, which means that the copolymer includes high crystalline regions and low crystalline regions, and the crystallinity distribution is wide and the free volume is small, so the charge mobility of the polymer is low and the volume resistivity is high. In addition, if the Tm-Tc value is too high, the volume resistivity may be reduced due to the low crystalline regions, and the transmittance may also be reduced due to the high crystalline regions. Specifically, when the Tm-Tc value is above 45°C, the content of the high crystalline region in the copolymer is low, and the problem of volume resistivity degradation may occur. When the Tm-Tc value is below 15°C, the crystallinity distribution of the copolymer may be excessively widened, and problems such as transmittance degradation due to the high crystalline regions and volume resistivity degradation due to the low crystalline regions may occur. In addition, if the density or melting temperature deviates from the above range, the problem of transmittance degradation may occur. It can be seen that the present invention achieves a good effect by regulating the ethylene / -olefin copolymer density, melting temperature and crystallization temperature, and obtain ethylene / -Olefin copolymers that can meet the application needs in the electrical and photovoltaic fields.
[0014] Wherein, the ethylene / The density of the olefin copolymer is 0.84-0.90 g / cc, for example, 0.85 g / cc, 0.86 g / cc, 0.87 g / cc, 0.88 g / cc or 0.89 g / cc, etc., preferably 0.87-0.88 g / cc.
[0015] The density in the present invention may refer to that measured according to ASTM D-792.
[0016] The melting temperature Tm having the maximum peak in the curve obtained by differential scanning calorimetry (DSC) is 40-90°C, for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C.
[0017] The curve obtained by differential scanning calorimetry has a crystallization temperature Tc with a maximum peak, and the melting temperature Tm is 15-45°C higher than the crystallization temperature Tc, for example, 20°C, 25°C, 30°C, 35°C or 40°C.
[0018] In the present invention, the melting temperature Tm and the crystallization temperature Tc are obtained by testing as follows:
[0019] In a nitrogen atmosphere, using a differential scanning calorimeter, the temperature of the copolymer was raised to 150°C, maintained for 5 minutes, lowered to -50°C, and then raised again, and the DSC curve was observed. In the measured DSC curve, the crystallization temperature is the maximum point of the exothermic peak during the first temperature drop, and the melting temperature is the maximum point of the endothermic peak during the second temperature rise.
[0020] Preferably, the ethylene / The weight average molecular weight of the olefin copolymer is 30,000-150,000 g / mol, for example, 40,000 g / mol, 50,000 g / mol, 60,000 g / mol, 80,000 g / mol, 100,000 g / mol, 120,000 g / mol or 140,000 g / mol.
[0021] Preferably, the ethylene / -The molecular weight distribution of the olefin copolymer is 1.8-2.5, for example, it can be 1.9, 2, 2.1, 2.2, 2.3 or 2.4, etc.
[0022] The present invention is carried out by treating ethylene / -The molecular weight distribution range of the olefin copolymer is limited to obtain a material with more excellent mechanical properties, avoiding the problems such as the increase in molecular weight distribution when two or more types of monomers are involved in the polymerization, resulting in a decrease in impact strength and mechanical properties, and possible blockage.
[0023] In the present invention, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene converted molecular weights analyzed by gel permeation chromatography (GPC), and the molecular weight distribution is calculated from the ratio of Mw / Mn.
[0024] Preferably, the crystallization temperature Tc is 25-45°C, for example, it may be 28°C, 30°C, 32°C, 35°C, 38°C, 40°C or 42°C, etc., more preferably 30-45°C.
[0025] Preferably, the ethylene / -The melt index of the olefin copolymer is 1-100 dg / min, for example, it can be 5 dg / min, 10 dg / min, 20 dg / min, 30 dg / min, 40 dg / min, 50 dg / min, 60 dg / min or 80 dg / min, and the melt index is tested at 190°C and 2.16 kg load conditions.
[0026] The present invention preferably comprises ethylene / -The melt index of the olefin copolymer makes it more suitable for the production application of encapsulation film; if the melt index is less than 1 dg / min, the production rate may be reduced due to high load, and if the melt index is greater than 100 dg / min, film molding is difficult and defects such as unsuitability for use as a sealing film may occur.
[0027] Preferably, the ethylene / -Olefin copolymers -Olefins selected from C4-C20 -Olefins, for example, C5, C6, C7, C8, C10, C12, C15 or C18 -Olefins, etc.
[0028] Preferably, the ethylene / -Olefin copolymers -Olefins include any one or a combination of at least two of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene or 1-eicosene, more preferably any one or a combination of at least two of 1-butene, 1-hexene or 1-octene, and even more preferably 1-butene, 1-hexene or a combination of 1-butene and 1-hexene.
[0029] In the present invention, ethylene / -Olefin copolymers -The olefin content can be appropriately selected within the range satisfying the physical conditions without limitation. Preferably, -Olefins in ethylene / -The molar content in the olefin copolymer is 0.01-99%, for example, it can be 0.5%, 1%, 2%, 5%, 10%, 20%, 30%, 50% or 80%, and more preferably 10-50%.
[0030] In a second aspect, the present invention provides an ethylene / - A method for preparing an olefin copolymer, the method comprising the following steps:
[0031] Ethylene and -olefins are polymerized in the presence of a transition metal compound catalyst to obtain the ethylene / -Olefin copolymers.
[0032] Preferably, the transition metal compound catalyst comprises a combination of a compound represented by formula I and a compound represented by formula II:
[0033] Formula I;
[0034] wherein R1 and R2 are each independently hydrogen, a C1-C20 (e.g., C2, C4, C6, C8, C10, C12, C14, C16, or C18, etc.) straight or branched alkyl, a C3-C20 (e.g., C4, C6, C8, C10, C12, C14, C16, or C18, etc.) cycloalkyl, a C2-C20 (e.g., C3, C4, C6, C8, C10, C12, C14, C16, or C18, etc.) alkenyl, a C1-C20 (e.g., C2, C4, C6, C8, C10, C12, C14, C16, or C18, etc.) , C14, C16 or C18, etc.), alkoxyl group of C6-C20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.), aryl group of C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.), arylalkoxyl group of C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.), alkylaryl group of C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.), arylalkyl group of C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.);
[0035] R3 and R4 are each independently hydrogen, halogen, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight chain or branched alkyl, C3-C20 (for example, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) cycloalkyl, C2-C20 (for example, C3, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) C6 or C18, etc.), alkenyl, C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.), arylalkoxy, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.), alkylamido, C6-C20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.), arylamido;
[0036] Q1 is Si, C or Ge;
[0037] M1 is Ti, Hf or Zr;
[0038] Formula II;
[0039] Wherein, R5 and R6 are each independently hydrogen, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight chain or branched alkyl, C3-C20 (for example, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) cycloalkyl, C2-C20 (for example, C3, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkenyl, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkoxy, C6-C20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.) aryl, C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.) arylalkoxy, C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.) alkylaryl, C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.) arylalkyl;
[0040] R7 is hydrogen, halogen, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight chain or branched alkyl, C3-C20 (for example, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) cycloalkyl, C2-C20 (for example, C3, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkenyl, C6-C20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.) C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.) aryl, C7-C20 (for example, C8, C9, C10, C12, C14, C16 or C18, etc.) arylalkyl, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkylamido, C6-C20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.) arylamido;
[0041] R8-R 12Each of them is independently hydrogen, halogen, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight chain or branched alkyl, C3-C20 (for example, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) cycloalkyl, C2-C20 (for example, C3, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkenyl, C1-C20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkoxy, C6-C20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.) aryl;
[0042] Q2 is Si, C or Ge;
[0043] M2 is Ti, Hf or Zr.
[0044] The present invention prepares ethylene / -olefin copolymer. Due to the structural characteristics of the catalyst, the transition metal compound represented by formula I is difficult to -Olefin monomers are introduced into the polymerization, tending to prepare copolymers with high density regions. The transition metal compound represented by formula II can -Olefins are introduced into the polymerization to prepare polymers in the extremely low density region (elastomers). The density of ethylene / olefin copolymers is affected by the type and amount of monomers used for polymerization, the degree of polymerization, etc., and in the case of copolymers, is largely affected by the amount of comonomer. In this case, if the amount of comonomer is increased, a low-density ethylene / olefin copolymer can be prepared. -olefin copolymers, and the amount of comonomer introduced into the copolymer is determined by the inherent copolymerization properties of the catalyst. Therefore, if one of the two transition metal compounds is used alone, mixing and introducing -Olefin-based monomers have different copolymerization properties, making it difficult to obtain ethylene / -Olefin copolymer materials. In addition, when two or more types of monomers are involved in the polymerization, the molecular weight distribution increases, resulting in reduced impact strength and mechanical properties, while the polymerization properties of different monomers depend on the catalyst. If the polymerization properties of the catalyst are very different, there will be a problem of increasing the molecular weight distribution of the polymer.
[0045] Therefore, the present invention adopts two catalysts with specific structures to adjust the material density, melting temperature and crystallization temperature, so that it exhibits high volume resistivity and light transmittance; on the other hand, it prepares ethylene / -Olefin copolymers prevent the degradation of the material's cross-linking properties, impact strength, mechanical properties, etc.
[0046] In the present invention, when the transition metal compound represented by formula I and the transition metal compound represented by formula II are used as catalysts, hydrogen can be selectively injected in a timely and appropriate amount during the polymerization reaction to prevent any β-hydride elimination reaction in the polymer chain and induce a uniform termination reaction to affect the weight-average molecular weight and melt index and reduce the molecular weight distribution of the polymer, thereby improving the crosslinking properties and mechanical properties while exhibiting high volume resistivity and transmittance.
[0047] Preferably, the molar ratio of the compound represented by formula I to the compound represented by formula II is 1:(1-5), wherein the specific value of (1-5) can be, for example, 1.5, 2, 2.5, 3, 3.5, 4 or 4.5.
[0048] Preferably, the compound represented by formula I is selected from any one or a combination of at least two of the compounds represented by formula I-1 to formula I-6:
[0049]
[0050] Formula I-1 Formula I-2 Formula I-3
[0051]
[0052] Formula I-4 Formula I-5 Formula I-6.
[0053] Preferably, the compound represented by formula II is selected from any one or a combination of at least two of the compounds represented by formula II-1 to formula II-12:
[0054]
[0055] Formula II-1 Formula II-2 Formula II-3
[0056]
[0057] Formula II-4 Formula II-5 Formula II-6
[0058]
[0059] Formula II-7 Formula II-8 Formula II-9
[0060]
[0061] Formula II-10 Formula II-11 Formula II-12.
[0062] Preferably, the polymerization is carried out in the presence of a cocatalyst.
[0063] Preferably, the promoter comprises an organic substance containing a Group IIIA element.
[0064] Preferably, the co-catalyst comprises any one or a combination of at least two of the compounds shown in Formula III to Formula V:
[0065] -[Al(R a )-O] n -
[0066] Formula III;
[0067] Among them, R a are the same as or different from each other, and are each independently halogen, C1-10 (for example, C2, C3, C4, C5, C6 or C8, etc.) straight chain or branched chain alkyl, halogen-substituted C1-10 (for example, C2, C3, C4, C5, C6 or C8, etc.) straight chain or branched chain alkyl;
[0068] n≥2, for example, it can be 3, 4, 5, 6, 8, 10, 15 or 20;
[0069] A(R b )3
[0070] Formula IV;
[0071] Among them, R b are the same as or different from each other and are each independently halogen, C1-20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight or branched alkyl, halogen-substituted C1-20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight or branched alkyl, and A is selected from aluminum or boron;
[0072] [D] + [ZT4] -
[0073] Formula V;
[0074] Among them, [D] + It is an organic cation;
[0075] Z is a Group IIIA element;
[0076] T are the same or different from each other and are each independently R c Substituted or unsubstituted C6-20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.) aryl, R c Substituted or unsubstituted C1-20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkyl, wherein R cIt is halogen, C1-20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) straight chain or branched alkyl, C1-20 (for example, C2, C4, C6, C8, C10, C12, C14, C16 or C18, etc.) alkoxy or C6-20 (for example, C7, C8, C10, C12, C14, C16 or C18, etc.) phenoxy.
[0077] Preferably, the compound represented by formula III includes any one of methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, butylaluminoxane or octylaluminoxane, or a combination of at least two thereof.
[0078] Preferably, the compound as shown in formula IV includes trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, monomethylaluminum dichloride, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethoxymethylaluminum, monomethoxydimethylaluminum, dimethylethylaluminum, trimethylboron, triethylboron, tripropylboron, tributylboron, triisobutylboron, etc., preferably any one of trimethylaluminum, triethylaluminum, triisobutylaluminum or trioctylaluminum, or a combination of at least two thereof.
[0079] Preferably, the [D] + It is an organic ammonium ion, phosphonium ion or carbonium ion.
[0080] Preferably, Z is aluminum or boron.
[0081] Preferably, the compound as shown in formula V includes triethylammonium tetra(phenyl)boron, tributylammonium tetra(phenyl)boron, trimethylammonium tetra(phenyl)boron, tripropylammonium tetra(phenyl)boron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o-, p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylaluminum tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, N,N-diethylanilinium tetra(phenyl)boron, N,N-dimethylanilinium tetra(phenyl)boron, Diethylammonium tetra(pentafluorophenyl)boron, triphenylphosphonium tetra(phenyl)boron, trimethylphosphonium tetra(phenyl)boron, triethylammonium tetra(phenyl)aluminum, tributylammonium tetra(phenyl)aluminum, trimethylammonium tetra(phenyl)aluminum, tripropylammonium tetra(phenyl)aluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o-, p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetra(pentafluorophenyl)aluminum, N ,N-dimethylanilinium tetra(phenyl)aluminum, N,N-diethylanilinium tetra(phenyl)aluminum, N,N-diethylanilinium tetra(pentafluorophenyl)aluminum, diethylammonium tetra(pentafluorophenyl)aluminum, triphenylphosphonium tetra(phenyl)aluminum, trimethylphosphonium (phenyl)aluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o-, p-dimethylphenyl)boron, trimethylphosphonium tetra(phenyl)aluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o-, p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbonium tetra(pentafluorophenyl)boron, triphenylcarbonium tetra(octafluoronaphthyl)boron, triethylammonium tetra(octafluoronaphthyl)boron, N ,N-dimethylaniliniumtetra(octafluoronaphthyl)boron or N,N-diethylaniliniumtetra(octafluoronaphthyl)boron, any one or a combination of at least two thereof.
[0082] Preferably, the molar ratio of the co-catalyst to the transition metal compound catalyst is 1:(1-1000), wherein the specific value of (1-1000) can be, for example, 5, 10, 50, 100, 200, 500 or 800.
[0083] In the present invention, a specific ratio of co-catalyst and transition metal compound catalyst is used to work together to achieve optimization of activity and control of polymer structure, with excellent catalytic effect. Excessive use may significantly reduce the effect and fail to obtain the desired target polymer.
[0084] Preferably, the polymerization is carried out in the presence of a solvent.
[0085] Preferably, the solvent is -The mass ratio of olefins is (0.5-50):1, wherein the specific value of (0.5-50) can be, for example, 1, 2, 5, 10, 20, 30 or 40.
[0086] Preferably, the solvent comprises a hydrocarbon solvent.
[0087] Preferably, the hydrocarbon solvent includes any one of aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, and halogenated hydrocarbons, or a combination of at least two of them.
[0088] Preferably, the polymerization temperature is 100-150°C, for example, 105°C, 110°C, 120°C, 130°C or 140°C.
[0089] Preferably, the polymerization pressure is 1-5 MPa, for example, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa or 4.5 MPa.
[0090] Preferably, the polymerization time is 10-60 min, for example, 15 min, 20 min, 30 min, 40 min or 50 min.
[0091] In the third aspect, the present invention provides an ethylene / -Application of olefin copolymers in optoelectronic devices.
[0092] The ethylene / -Olefin copolymers can be used in various molded products by extrusion molding, etc., in particular, ethylene / -Olefin copolymers can be used in various optoelectronic devices, for example, as sealants for encapsulating devices in solar cells, but are not limited thereto.
[0093] On the other hand, the present invention provides a packaging film, wherein the raw materials for preparing the packaging film include, by weight: ethylene / -100 parts of olefin copolymer, 0.1-5 parts of crosslinking agent (for example, 0.2 parts, 0.5 parts, 1 parts, 2 parts, 3 parts or 4 parts, etc.), 0.5-5 parts of initiator (for example, 0.8 parts, 1 parts, 2 parts, 3 parts or 4 parts, etc.).
[0094] Preferably, the raw materials for preparing the encapsulation film further include 0.05-1 part of a coupling agent, for example, 0.1 part, 0.2 part, 0.3 part, 0.5 part or 0.8 part, etc., by weight.
[0095] Compared with the prior art, the present invention has at least the following beneficial effects:
[0096] The ethylene / -Olefin copolymers meet the specific range of specific density, specific melting temperature and the difference between melting temperature and crystallization temperature measured by DSC. The products such as adhesive films made from them show high volume resistance and excellent light transmittance, with a volume resistance of ≥1016 , transmittance>90%. When used in photovoltaic devices, it can delay the PID phenomenon and achieve excellent module efficiency. DETAILED DESCRIPTION
[0097] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0098] The materials used in the following examples are all commercially available products.
[0099] In one specific embodiment, the transition metal compound catalyst having the structure shown in Formula I can be prepared by the following method:
[0100] .
[0101] In one specific embodiment, the transition metal compound catalyst having the structure shown in Formula II can be prepared by the following method:
[0102] .
[0103] Preparation Example 1
[0104] A transition metal compound catalyst I-1, the structure of the transition metal compound catalyst is shown in formula I-1, and the transition metal compound catalyst is prepared by the following method:
[0105]
[0106] (1) In a 150 mL reactor equipped with a stirrer, a dropping funnel and a drying tube with calcium chloride, concentrated sulfuric acid (18 mol / L, 51.9 g, 0.53 mol) was added to the reaction bottle as a cyclization catalyst. The mixture was cooled to -10°C to 0°C in an ice-salt bath and stirred. Compound A (37.5 g, 176.8 mmol) was added dropwise thereto. The temperature was maintained for 2 h. When the raw materials were completely consumed, the reaction was stopped. The reaction solution was poured into 100 mL of ice-water solution, and a saturated aqueous solution of sodium hydroxide (75.2 g, 1.88 mol) was slowly added dropwise to the reaction solution. The pH value was adjusted to 8-10, and the mixture was extracted with ethyl acetate for 3 times, using 400 mL of ethyl acetate each time. After drying with 30 g of anhydrous magnesium sulfate, the mixture was concentrated under reduced pressure to remove the solvent. A yellow liquid was obtained by concentration, and compound B (33.7 g) was obtained by distillation under reduced pressure. The yield was 89.6%.
[0107] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.91(6H,s),1.77(2H,dd),1.82(3H,dd),3.06(2H,dd),3.22(3H,dd),5.28(1H,s),6.21-6.36(2H,tt),7.06(1H,dd).
[0108] (2) Place tert-butyl chloride (347 mg, 3.75 mmol) in a 25 mL two-necked reaction bottle, evacuate and protect with nitrogen, add 11 mL of anhydrous dimethylacetamide (DMA) solvent, then add N,N-diisopropylethylamine (DIPEA, 1.5 mL, 9.3 mmol) dropwise, stir at room temperature for 5 min, then add compound B (0.79 g, 3.75 mmol) dropwise, then gradually heat to 100 °C, react for about 7 h, and cool the reaction after TLC detection is complete. The mixture was stirred for 2 hours, and then an appropriate amount of 1 mol / L hydrochloric acid solution was added to adjust the pH value to acidic, and then an appropriate amount of saturated NaHCO3 solution was added to adjust the pH value to neutral, distilled water was added, and the mixture was extracted three times with dichloromethane. The organic phases were combined and then washed with saturated saline solution. The organic phase was dried over anhydrous magnesium sulfate and then concentrated to dryness under reduced pressure to obtain a yellow oily liquid crude product, which was separated by silica gel chromatography (eluted with an eluent of petroleum ether and ethyl acetate in a volume ratio of 5:1) to obtain a light yellow solid compound C (562 mg) with a yield of 56%.
[0109] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.90(6H,s),1.44(9H,s)1.75(2H,dd),1.80(3H,dd),3.22(2H,dd),3.37(2H,dd),6.36-6.38(2H,tt),7.10(1H,dd).
[0110] (3) Compound C (536 mg, 2 mmol) was placed in a 250 mL reaction bottle, and 150 mL of dry tetrahydrofuran (THF) solution was added. After evacuation, the mixture was protected by nitrogen and cooled to -10°C to 0°C in an ice-salt bath. Under stirring, n-butyl lithium (n-BuLi, 1.6 mol / L, 1.4 mL, 2.2 mmol) was added dropwise. After the addition was complete, the reaction was warmed to room temperature and stirred for 30 min. Dimethylsilyl tert-butylamine trifluoromethanesulfonic acid (0.5 g, 2 mmol) was added and the reaction was stirred overnight. After the reaction was completed, the mixture was filtered on dry diatomaceous earth and the filtrate was concentrated to obtain oily compound D (675 mg) with a yield of 85%.
[0111] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.11(6H,s)0.90(6H,s),1.27(9H,d),1.44(9H,s),1.75(2H,dd),1.79(3H,dd ),2.0(1H,dd),3.37(2H,dd),3.52(1H,dd),6.34-6.37(2H,tt),7.12(1H,dd).
[0112] (4) Add 5 g of compound D (12.7 mmol) and 250 mL of dry n-hexane to a 500 mL three-necked round-bottomed reaction bottle, and add 6 mL of n-butyl lithium (15 mmol) dropwise at -30°C. Control the temperature below -30°C and complete the addition in half an hour. Return to room temperature and stir for 6 hours. The solution turns into a white turbid liquid. Then add the solution to another 500 mL three-necked round-bottomed reaction bottle containing 4.24 g of TiCl4 (2THF) (12.7 mmol) in dry n-hexane at 5°C. Add the solution in 40 minutes. Stir at room temperature for 3 hours. The solution turns from light yellow to brown yellow. After the reaction is completed, filter and wash with dry toluene. The filtrate is then dried and transferred to a glove box. Add dry n-hexane at -20°C for low-temperature recrystallization. Vacuum dry for two hours to obtain 2.75 g of yellow powder, which is a CGC-type dichlorotitanium complex having the structure shown in Ⅰ-1. The yield is 41% and the purity is 98%.
[0113] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.15(6H,s)0.92(6H,s),1.30(9H,d),1.45(9H,s),1.75(2H,dd),1.79(3H,dd),3.37(2H,dd),6.37-6.40(2H,tt),7.1(1H,dd).
[0114] Preparation Example 2
[0115] A transition metal compound catalyst II-5, the structure of which is shown in formula II-5. The preparation method of the transition metal compound catalyst is different from that of Preparation Example 1 only in that in step (3), dimethylsilyl tert-butylamine trifluoromethanesulfonic acid is replaced with an equimolar amount of (3,5-xylyl)(methyl)silyl tert-butylamine trifluoromethanesulfonic acid, and other materials, amounts and preparation methods are the same as those of Preparation Example 1. The reaction can obtain 2.74 g of light yellow powder with a yield of 35% and a purity of 98%.
[0116] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.65(3H,s),0.92(6H,s),1.30(9H,d),1.45(9H,s),1.75(2H,dd),1.79(3H,dd), 2.35(6H,s),3.37(2H,dd),6.37-6.40(2H,tt),6.89-7.1(3H,dd),7.35(1H,dd).
[0117] Preparation Example 3
[0118] A transition metal compound catalyst II-6, the structure of which is shown in formula II-6. The preparation method of the transition metal compound catalyst is different from that of Preparation Example 1 only in that in step (3), dimethylsilyl tert-butylamine trifluoromethanesulfonic acid is replaced with an equimolar amount of (4-methoxyphenyl) (methyl)silyl tert-butylamine trifluoromethanesulfonic acid, and other materials, amounts and preparation methods are the same as those of Preparation Example 1. The reaction can obtain 4.08 g of white powder with a yield of 52% and a purity of 97%.
[0119] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.72(3H,s),0.92(6H,s),1.30(9H,d),1.45(9H,s),1.75(2H,dd),1.83(3 H,dd),3.32(2H,dd),3.83(3H,t),6.37-6.40(2H,tt),6.91-7.15(5H,dd).
[0120] Preparation Example 4
[0121] A transition metal compound catalyst II-7, the structure of which is shown in formula II-7. The preparation method of the transition metal compound catalyst is different from that of Preparation Example 1 only in that in step (3), dimethylsilyl tert-butylamine trifluoromethanesulfonic acid is replaced with an equimolar amount of (3,5-diisopropylphenyl) (methyl)silyl tert-butylamine trifluoromethanesulfonic acid, and other materials, amounts and preparation methods are the same as those of Preparation Example 1. The reaction can obtain 3.85 g of yellow powder with a yield of 45% and a purity of 95%.
[0122] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.66(3H,s),0.92(6H,s),1.20(12H,s),1.31(9H,d),1.45(9H,s),1.75(2H,dd),1 .79(3H,dd),2.87(2H,dd),3.37(2H,dd),6.37-6.40(2H,tt),6.97-7.25(4H,dd).
[0123] Preparation Example 5
[0124] A transition metal compound catalyst II-8, the structure of which is shown in formula II-8. The preparation method of the transition metal compound catalyst is different from that of Preparation Example 1 only in that in step (3), dimethylsilyl tert-butylamine trifluoromethanesulfonic acid is replaced with an equimolar amount of (3,5-di-tert-butylphenyl) (methyl)silyl tert-butylamine trifluoromethanesulfonic acid, and other materials, amounts and preparation methods are the same as those of Preparation Example 1. The reaction can obtain 2.84 g of bright yellow powder with a yield of 32% and a purity of 95%.
[0125] NMR characterization results: 1 H NMR (400MHz,CDCl3) 0.66(3H,s),0.92(6H,s),1.27(9H,t),1.35(18H,s),1.42(9H,s),1.75(2 H,dd),1.82(3H,s),3.37(2H,dd),6.37-6.40(2H,tt),7.2-7.55(4H,dd).
[0126] Example 1
[0127] A kind of ethylene / -olefin copolymer, the ethylene / -Olefin copolymers are prepared by the following method:
[0128] Use a metering pump to add 500 mL of Isoper E and 300 mL of 1-octene to a 2 L stainless steel reactor, add 2.5 mL of modified methylaluminoxane (MMAO-7, Nouryon, Tianjin), introduce ethylene and maintain the pressure at 3 MPa, raise the temperature to 130°C, start stirring, add a mixture of the transition metal compound catalyst Ⅰ-1 (1.4 µmol) obtained in Preparation Example 1 and the transition metal compound catalyst Ⅱ-5 (3.2 µmol) obtained in Preparation Example 2 into the spare small chamber of the reactor, maintain 3.5 MPa of nitrogen, then add it into the reactor, react at 130°C for 30 min, after the reaction is completed, depressurize the system, replace with nitrogen three times, discharge the polymerization solution into a beaker containing 500 mL of ethanol, filter the precipitated polymer, and dry it in a vacuum oven for 12 hours to obtain the ethylene / -Olefin copolymers.
[0129] Examples 2-6, Comparative Examples 1-7
[0130] A kind of ethylene / -olefin copolymer, which differs from Example 1 in that ethylene / -Olefin copolymers are prepared using different catalysts and 1-octene dosages, as shown in Table 1; The preparation method of the olefin copolymer is the same as that in Example 1.
[0131] Table 1
[0132]
[0133] Ethylene / -Olefin copolymers were tested as follows:
[0134] 1) Density: Tested according to ASTM D-792 standard.
[0135] 2) Molecular weight and molecular weight distribution (MWD) of polymers: The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymers were measured by using a high temperature GPC-IR method, and the molecular weight distribution was calculated by dividing the weight average molecular weight by the number average molecular weight. The test temperature was 150°C, polystyrene was used as the standard, trichlorobenzene was used as the solvent, and the flow rate was 1.0 mL / min.
[0136] 3) Melt index MI of polymer 2.16 : Measured according to ASTM D 1238 at 190°C under a load of 2.16 kg and expressed as the weight of the molten polymer in 10 minutes.
[0137] 4) Crystallization temperature (Tc) and melting temperature (Tm): In a nitrogen atmosphere, using a differential scanning calorimeter (DSC 6000) manufactured by PerkinElmer, the temperature of the copolymer was raised to 150°C, maintained for 5 minutes, lowered to -50°C, and then raised again, and the DSC curve was observed. In this case, the heating rate and the cooling rate were 10°C / min, respectively. In the measured DSC curve, the crystallization temperature is the maximum point of the exothermic peak during the first temperature reduction, and the melting temperature is the maximum point of the endothermic peak during the second temperature increase.
[0138] The test results are summarized in Table 2.
[0139] Table 2
[0140] Application Examples 1-6, Comparative Application Examples 1-7
[0141] A packaging film composition is prepared by the following method:
[0142] To 500g of the ethylene obtained in Examples 1-6 and Comparative Examples 1-7 -olefin copolymer, injecting 1phr 1-(2-methyloctyl) tert-butyl peroxycarbonate, 0.5phr triallyl isocyanurate (TAIC) and 0.2phr methacryloxypropyl trimethoxysilane (MEMO), soaking at 50°C for 2 hours, aging for 15 hours, to obtain the sealant film composition;
[0143] Here, "phr" refers to the weight parts of the material per hundred weight parts of the copolymer.
[0144] A packaging film is prepared by the following method:
[0145] The above encapsulation film composition was placed in a 0.5T square frame, with 3T steel plates on the front and back, and injected into a high-temperature press. 2 After continuous treatment (240 seconds), decompression / compression degassing was performed 6 times, and the pressure was increased by 151N / cm at 190℃. 2 The treatment was continued for 240 seconds, and then the temperature was reduced to 30°C at 15°C / min, and the pressure was maintained at 151N / cm 2 , at 30℃, 151N / cm 2 The process was maintained for 300 seconds to obtain the packaging adhesive film.
[0146] The above encapsulation film was tested as follows:
[0147] 1) Volume resistance: measured using an Agilent 4339B high resistance meter (product of Agilent Technologies) under the conditions of temperature of 23±1°C and humidity of 50±3% by applying a voltage of 1000 V for 60 seconds.
[0148] 2) Transmittance: The transmittance at 550 nm was measured using a Shimadzu UV-3600 spectrophotometer, with a wavelength interval of 1 nm and a measurement rate of medium.
[0149] The test results are summarized in Table 3.
[0150] Table 3
[0151]
[0152] It can be seen from the test results that the present invention limits ethylene / -olefin copolymer density, melting temperature and crystallization temperature, and thus obtain a film material with high volume resistance and excellent light transmittance, with a volume resistance of ≥1.0×10 16 Ω·cm, and light transmittance ≥91.1%, meeting the application requirements in electrical, photovoltaic and other fields.
[0153] By comparing Examples 1-6 with Comparative Examples 1-7, it can be seen that when ethylene / When the density of the olefin copolymer is too large or too small, or the Tm-Tc is too large or too small, the volume resistivity of the material is significantly reduced, the transmittance is degraded, and it is difficult to exhibit suitable physical properties in the sealant film of the solar cell.
[0154] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. Ethylene / -Olefin copolymer, characterized in that The ethylene / -Olefin copolymers have the following characteristics: (a) the ethylene / - the density of the olefin copolymer is 0.84-0.90 g / cc; (b) a melting temperature Tm having a maximum peak in a curve obtained by a differential scanning calorimeter is 40-90°C; (c) A crystallization temperature Tc having a maximum peak in a curve obtained by a differential scanning calorimeter, and the melting temperature Tm is 15-45° C. higher than the crystallization temperature Tc.
2. Ethylene according to claim 1 / -Olefin copolymer, characterized in that The ethylene / - the weight average molecular weight of the olefin copolymer is 30000-150000 g / mol; The ethylene / - The molecular weight distribution of the olefin copolymer is 1.8-2.5; The crystallization temperature Tc is 25-45°C; The ethylene / The melt index of the olefin copolymer is 1-100 dg / min, and the melt index is measured at 190° C. and 2.16 kg load.
3. Ethylene according to claim 1 / -Olefin copolymer, characterized in that The ethylene / -Olefin copolymer -Olefins selected from C4-C20 - olefins; Said -Olefins in ethylene / - The molar content in the olefin copolymer is 0.01-99%.
4. An ethylene / - A method for preparing an olefin copolymer, characterized in that The preparation method comprises the following steps: Ethylene and -olefins are polymerized in the presence of a transition metal compound catalyst to obtain the ethylene / -Olefin copolymers.
5. The preparation method according to claim 4, characterized in that: The transition metal compound catalyst comprises a combination of a compound represented by formula I and a compound represented by formula II: Formula I; wherein R1 and R2 are each independently hydrogen, C1-C20 straight or branched alkyl, C3-C20 cycloalkyl, C2-C20 alkenyl, C1-C20 alkoxy, C6-C20 aryl, C7-C20 arylalkoxy, C7-C20 alkylaryl, C7-C20 arylalkyl; R3 and R4 are each independently hydrogen, halogen, C1-C20 straight or branched alkyl, C3-C20 cycloalkyl, C2-C20 alkenyl, C7-C20 arylalkoxy, C1-C20 alkylamido, C6-C20 arylamido; Q1 is Si, C or Ge; M1 is Ti, Hf or Zr; Formula II; wherein R5 and R6 are each independently hydrogen, C1-C20 straight or branched alkyl, C3-C20 cycloalkyl, C2-C20 alkenyl, C1-C20 alkoxy, C6-C20 aryl, C7-C20 arylalkoxy, C7-C20 alkylaryl, C7-C20 arylalkyl; R7 is hydrogen, halogen, C1-C20 straight or branched alkyl, C3-C20 cycloalkyl, C2-C20 alkenyl, C6-C20 aryl, C7-C20 alkylaryl, C7-C20 arylalkyl, C1-C20 alkylamido, C6-C20 arylamido; R8-R 12 Each is independently hydrogen, halogen, C1-C20 straight or branched alkyl, C3-C20 cycloalkyl, C2-C20 alkenyl, C1-C20 alkoxy, C6-C20 aryl; Q2 is Si, C or Ge; M2 is Ti, Hf or Zr; The molar ratio of the compound represented by formula I to the compound represented by formula II is 1:(1-5).
6. The preparation method according to claim 5, characterized in that: The compound represented by Formula I is selected from any one or a combination of at least two of the compounds represented by Formula I-1 to Formula I-6: ; Formula I-1 Formula I-2 Formula I-3 ; Formula I-4 Formula I-5 Formula I-6; The compound represented by Formula II is selected from any one or a combination of at least two of the compounds represented by Formula II-1 to Formula II-12: ; Formula II-1 Formula II-2 Formula II-3 ; Formula II-4 Formula II-5 Formula II-6 ; Formula II-7 Formula II-8 Formula II-9 ; Formula II-10 Formula II-11 Formula II-12.
7. The preparation method according to claim 4, characterized in that: The polymerization is carried out in the presence of a co-catalyst; The promoter includes an organic substance containing a Group IIIA element.
8. The preparation method according to claim 7, characterized in that: The co-catalyst includes any one or a combination of at least two of the compounds shown in Formula III to Formula V: <h2 style=";text-align:left;direction:ltr">-[Al(R<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> )-O]<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> - Formula III; Among them, R a are the same as or different from each other, and are each independently halogen, C1-10 straight or branched alkyl, or halogen-substituted C1-10 straight or branched alkyl, and n≥2; A(R b )3 Formula IV; Among them, R b are the same as or different from each other and are each independently halogen, C1-20 straight or branched alkyl, C1-20 straight or branched alkyl substituted with halogen, and A is selected from aluminum or boron; [D] + [ZT4] - Formula V; Among them, [D] + It is an organic cation; Z is a Group IIIA element; T are the same or different from each other and are each independently R c Substituted or unsubstituted C6-20 aryl, R c Substituted or unsubstituted C1-20 alkyl, said R c is halogen, C1-20 straight or branched alkyl, C1-20 alkoxy or C6-20 phenoxy; The molar ratio of the co-catalyst to the transition metal compound catalyst is 1:(1-1000).
9. The preparation method according to claim 4, characterized in that: The polymerization temperature is 100-150°C; The polymerization pressure is 1-5MPa; The polymerization time is 10-60 min.
10. An ethylene / -Application of olefin copolymers in optoelectronic devices.
Citation Information
Patent Citations
Olefin-based polymer and method for preparing same
CN102971346A
An ethylene / alpha-olefin copolymer having excellent electrical insulation properties
CN112592422A
Novel metallocene catalyst and use thereof
CN117396523A
Silylated and N-silylated compound synthesis
US20010056199A1
Ethylene / α-olefin copolymer and preparation method therefor
WO2019212303A1
